Integrasi Nilai-Nilai Al-Qur'an dan Hadis dalam Manajemen Kurikulum Pendidikan Islam: Kajian Teoritis - Refnawati, Refnawati; Bustamam, Risman; Misrawani, Misrawani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to understand the integration of the values of the Qur'an and Hadith in the management of Islamic education curriculum: a theoretical study. This research uses a library research method that is qualitative-theoretical in nature. The primary sources include the Qur'an, the Hadith of the Prophet Muhammad (peace be upon him), as well as relevant books of tafsir and explanations of Hadith. Secondary sources include scholarly books, academic journals, dissertations, and educational policy documents related to curriculum management and Islamic education. Data analysis is conducted descriptively-qualitatively, with a content analysis approach to the content of the literature being studied. The results of the analysis are then synthesized to formulate a conceptual model or framework of thought. The results of the data analysis show that the use of terms in education based on the Qur'an and Sunnah is crucial, as it will influence the concept of education, especially education in the Islamic sense. The understanding of education will underpin the goals, methods, and even the curriculum of education itself. Merely adopting all terms or combining them as an effort to accommodate is not sufficient, given that their structure and emphasis will differ. If ta’dib is the term that best represents education in Islam, then adab will become a focal point in overall education, not just in religious education. The process of self-development and teaching is an essential part of education to achieve the goals of humans as servants of Allah.